The song of Bertrand Du Guesclin - Cuvelier, trouvère, active 14th century (Boydell Press, 2019)
Bertrand du Guesclin was one of the main architects of the recovery of France. From humble beginnings he rose to become one of the great heroic figures of French history. This is the first English translation of Cuvelier's epic poem about him.